1996
DOI: 10.1139/o96-083
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase: a key enzyme in collagen turnover

Abstract: The primary agents responsible for cartilage and bone destruction in joint diseases are active proteinases that degrade collagen and proteoglycan. All four main classes of proteolytic enzymes are involved in either the normal turnover of connective tissue or its pathological destruction. These proteinases are made by different cells found within the joints. Both extracellular and intracellular pathways exist and individual enzymes can be inhibited by specific proteinaceous inhibitors that block their activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 136 publications
1
76
0
5
Order By: Relevance
“…Excessive degradation of type I collagen is associated with a variety of human diseases, such as arthritis, tumor metastasis, and atherosclerosis [22]. Collagenases (such as MMP-1, MMP-8, and MMP-13) are able to cleave fibrillar collagen I, leading to the formation of two fragments corresponding approximately to and fragments of the mature collagen molecule [31,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive degradation of type I collagen is associated with a variety of human diseases, such as arthritis, tumor metastasis, and atherosclerosis [22]. Collagenases (such as MMP-1, MMP-8, and MMP-13) are able to cleave fibrillar collagen I, leading to the formation of two fragments corresponding approximately to and fragments of the mature collagen molecule [31,45].…”
Section: Discussionmentioning
confidence: 99%
“…The triple helix is made of two a-1 chains and one a-2 chain, and this structural assembly is characterized by a typical dichroic signal, peaking at 224 nm [20], which decreases only upon gross unwinding. Since physiological collagenolysis is crucial for several biological processes, such as tissue repair and remodeling, angiogenesis, and wound healing [3,21], and collagenases are the main MMPs involved in collagen turnover and remodeling [22][23][24], a clarification of the mechanism of processing of the triple helix by collagenases is of the utmost importance. Structural data on fibrillar collagen I [25][26][27] indeed have shown that, on the basis of the available three-dimensional structures of collagenases [28,29], the triple-helical structural assembly does not allow collagen I to come into close contact with the catalytic site of collagenases.…”
Section: Introductionmentioning
confidence: 99%
“…The human MMP gene family contains 24 identified members in four major groups -the collagenases, gelatinases, stromelysins, and MT-MMPs (Shingleton et al, 1996). The collagenases (MMP-1, MMP-8, and MMP-13) cleave triple helical collagen into two fragments; gelatinases (MMP-2 and MMP-9) degrade denatured collagen; and stromelysins (MMP-3, MMP-7, MMP-10 and MMP-11) degrade a broad range of molecules, including aggrecan, fibronectin, laminin and procollagens.…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical studies invariably show that the mechanical stability of the arterial wall essentially relies on fibrillar collagens in media and adventitia. 4 -6 These structural collagens are highly resistant toward proteolytic degradation, and the only mammalian proteases that have been shown to cleave the native triple helical region of fibrillar collagen are the classic collagenases of the MMP family 7 [ie, MMP-1, -8, and -13 and the membrane type-1 MMP (MT-1 MMP or MMP-14 8 )], as well as selected members of the cysteine protease family (ie, cathepsin K, 9,10 L, 11 and possibly S 12 ).…”
mentioning
confidence: 99%